Awareness of the future among university students (Journal of the College of Basic Education, 2022)
The current research aims to identify the awareness of the future among university students and to identify the significance of the differences between the research sample according to the gender variable (males, females). A sample consisting of (400) university students. The sample was randomly selected in the College of Basic Education - Al-Mustansiriyah University. The researchers extracted the psychometric characteristics of the scale and used statistical indicators. The research reached results, including that university students have a percentage of awareness of the future, and the results also indicate the presence of Statistically significant differences between the average students of the College of Basic Education (male-female) on the scale of awareness of the future and in favor of males. In light of the results of the research, the researcher recommended a set of recommendations and suggestions.